Platforms for institutional change: assessing the potential of livelihood enhancement groups as community entry points in Zambia - Mulungu, K.; Madzudzo, E.; Adjei-Nsiah, Samuel; Akatama, M. (Informa UK Limited, 2017)
To address the livelihood problems faced by the poor and vulnerable in Northern Province of Zambia, a novel collective action approach called livelihoods enhancement groups (LEGs) was used as a platform for facilitating research on development initiatives to generate change. Using focus group discussions and key informant interviews, this article assesses the potential of using the LEGs approach in generating change. The livelihood changes observed arose with the LEG as a platform through which different knowledge nodes interacted. Livelihood areas that LEGs affected included crop production, livestock production, nutrition, and access to credit.